Dimerization of quercetin, Diels-Alder vs. radical-coupling approach: a joint thermodynamics, kinetics, and topological study - Fourré, Isabelle; Di Meo, Florent; Podloucká, Pavlína; Otyepka, Michal; Trouillas, Patrick (Journal of molecular modeling, 2016)
Quercetin is a prototypical antioxidant and prominent member of flavonoids, a large group of natural polyphenols. The oxidation of quercetin may lead to its dimerization, which is a paradigm of the more general polyphenol oligomerization. There exist two opposing mechanisms to describe the dimerization process, namely radical-coupling or Diels-Alder reactions. This work presents a comprehensive rationalization of this dimerization process, acquired from density functional theory (DFT) calculations. It is found that the two-step radical-coupling pathway is thermodynamically and kinetically preferred over the Diels-Alder reaction. This is in agreement with the experimental results showing the formation of only one isomer, whereas the Diels-Alder mechanism would yield two isomers. The evolution in bonding, occurring during these two processes, is investigated using the atoms in molecules (AIM) and electron localization function (ELF) topological approaches. It is shown that some electron density is accumulated between the fragments in the transition state of the radical-coupling reaction, but not in the transition state of the Diels-Alder process. Graphical Abstract Quantum chemistry calculations of the dimerization process of quercetin show that a radical coupling approach is preferred to a Diels-Alder type reaction, in agreement with experimental results. Analysis of the bonding evolution highlights the reaction mechanism.
Keywords: Thermochemistry; Atoms in molecules (AIM); Flavonoids; Electron localization function (ELF); Antioxidants; Density functional theory; Kinetics